PENINGKATAN PENGETAHUAN DENGAN SOSIALISASI MENGENAI PENTINGNYA MENJAGA KERAHASIAAN SERTIFIKAT VAKSIN MELALUI MEDIA SOSIAL - Andhi Nur Rahmadi; Nurul Jannah Lailatul Fitria; Meliana Putri (Dharma Pengabdian Perguruan Tinggi (DEPATI), 2021)
The phenomenon of giving Covid-19 vaccinations at a cost charged to the state budget for all Indonesian people. The phenomenon of giving free Covid-19 vaccinations for all Indonesian people. This program has attracted the enthusiasm of people throughout Indonesia, including in the City of Probolinggo. The public's enthusiasm is not only ready to receive the Covid-19 vaccine but also shows that the community has been vaccinated by posting vaccine certificates on social media. Of course, it creates a new polemic because the vaccine certificate displays a QR Code containing personal data belonging to the public. If irresponsible people can access these personal data, it can open opportunities for crime. This phenomenon also occurs in the Panca Marga University campus environment; there are still those who do not understand the importance of maintaining the confidentiality of vaccine certificates and the lack of awareness of children's data protection. This study uses a qualitative method. The researcher considers that the relevant qualitative research method is used as a method in this research. The method used in writing this community service is through a qualitative approach; researchers can provide information related to protecting the confidentiality of vaccine certificates by distributing posters, opening question and answer facilities, and voting on social media with the theme "Do not Spread Covid-19 Vaccination Certificates Carelessly". The results of community service show that to increase knowledge related to the protection of personal data contained in vaccine certificates by residents of the Panca Marga University campus, namely by socializing through social media